2011
DOI: 10.1007/s11136-011-9905-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal function is associated with worse self-reported outcomes after kidney transplantation

Abstract: Several health-related quality of life dimensions may be affected by poor renal function after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
5
16
0
Order By: Relevance
“…Overall, the KDQOL-36™ scores were similar to those reported in other US studies of non-dialysis CKD and kidney transplant recipients, 27,28 and higher than in dialysis patients. 29 Similar to findings from the Dialysis Outcomes and Practice Patterns Study, 29 we observed that Hispanics with CKD had lower HRQOL than non-Hispanics.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the KDQOL-36™ scores were similar to those reported in other US studies of non-dialysis CKD and kidney transplant recipients, 27,28 and higher than in dialysis patients. 29 Similar to findings from the Dialysis Outcomes and Practice Patterns Study, 29 we observed that Hispanics with CKD had lower HRQOL than non-Hispanics.…”
Section: Discussionsupporting
confidence: 84%
“…sick leave in the 12-month period prior to the interview and the number of comorbidities) components of work ability drove the association observed. CKD causes several changes in key physiological function that may directly or indirectly impair quality of life and well-being [9]. Hence, it is not surprising that the association between eGFR and WAI was attenuated after the inclusion of a marker of CKD-related anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects of immunosuppression and posttransplant complications contribute to loss of allograft function [5,6,7,8], which leads to reduced quality of life [9,10,11] and possibly impaired ability to work. Work ability is a dynamic process resulting from the interaction of individual resources (including health, functional capacity, generic and specific education, motivation), working conditions (environment, tools, psychosocial factors), and the society (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of utilities were derived from the study by Neri et al, 363 who reported EQ-5D health states measured in a cross-sectional study of people with kidney-only transplants in the UK, valued using UK tariffs, as a function of CKD states. As renal function deteriorated so did the HRQoL (utility) values experienced by the simulated patient in the model.…”
Section: Utilitiesmentioning
confidence: 99%